Spremembe sosedskih odnosov kot odziv na zahteve delovnega življenja? - Filipovič Hrast, Maša (Teorija in praksa, 2009)
The problem of reconciling work and family life is recognised and comprises the subject of much research. However, the influence of work on community life and neighbourly relations, which is a theme of this article, is not so well recognised and debated. The author analyses the influence of work status and importance ascribed to work on sense of community. The analysis is based on a small quantitative survey in two neighbourhoods in Ljubljana (Fužine and Murgle). The findings indicate that work status is not as important as the value of work, i.e. the importance ascribed to work. People who feel that work is important have a smaller sense of community, i.e. they socialise with their neighbours less, are less attached to their neighbourhood. On the other hand, people who value more friends, family and free time have a greater sense of community.
Keywords: Neighbourhood; Soseska; Sosedski odnosi; Neighbourhood relations; Delo; Labor; labour; Sociological aspects; Sociološki vidik; Ljubljana; stanovanjska naselja; stanovanjske soseske; družbeni odnosi; odnos do dela; vplivi; analize